Project management techniques - Sholarin, E.; Awange, Joseph (2015)
© 2015, Springer International Publishing Switzerland. Tools and techniques are widely used in many human endeavors, such as engineering, construction, banking, manufacturing, marketing, health care, sales, transportation, information technology, research and development, academics, legal, political and government establishments, just to mention a few.